Nicotiana attenuata NaHD20 plays a role in leaf ABA accumulation during water stress, benzylacetone emission from flowers, and the timing of bolting and flower transitions - Ré, Delfina Adela (2011)
Homeodomain-leucine zipper type I (HD-Zip I) proteins are plant-specific transcription factors associated with the regulation of growth and development in response to changes in the environment. Nicotiana attenuata NaHD20 was identified as an HD-Zip I-coding gene whose expression was induced by multiple stress-associated stimuli including drought and wounding. To study the role of NaHD20 in the integration of stress responses with changes in growth and development, its expression was silenced by virus-induced gene silencing (VIGS), and control and silenced plants were metabolically and developmentally characterized. Phytohormone profiling showed that NaHD20 plays a positive role in abscisic acid (ABA) accumulation in leaves during water stress and in the expression of some dehydration-responsive genes including ABA biosynthetic genes. Moreover, consistent with the high levels of NaHD20 expression in corollas, the emission of benzylacetone from flowers was reduced in NaHD20-silenced plants. Additionally, bolting time and the opening of the inflorescence buds was decelerated in these plants in a specific developmental stage without affecting the total number of flowers produced. Water stress potentiated these effects; however, after plants recovered from this condition, the opening of the inflorescence buds was accelerated in NaHD20-silenced plants. In summary, NaHD20 plays multiple roles in N. attenuata and among these are the coordination of responses to dehydration and its integration with changes in flower transitions.